2012
DOI: 10.1292/jvms.12-0056
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mitochondrial Genes of <i>Babesia gibsoni</i> in Resistance to Diminazene Aceturate

Abstract: aBsTracT. The stability of the characteristics of the diminazene aceturate (Da)-resistant B. gibsoni isolate was initially determined in vitro. Part of the Da-resistant B. gibsoni isolate was cultured without Da for 4 weeks, and then newly exposed to 200 ng/ml Da. as a result, this isolate could proliferate the same as the Da-resistant isolate, indicating that the characteristic of Da resistance was stable in the Daresistant isolate. additionally, the level of parasitemia in the Da-resistant isolate was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
(56 reference statements)
0
18
0
1
Order By: Relevance
“…The currently available anti-piroplasm drugs, diminazene aceturate (DA) and imidocarb dipropionate, have sometimes been reported to have toxic side effects 3 . In addition, DA-resistant Babesia gibsoni and the development of imidocarb dipropionate–resistant Theileria equi have been reported 4 , 5 . Therefore, less-toxic, low-cost and potent anti-piroplasm chemotherapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The currently available anti-piroplasm drugs, diminazene aceturate (DA) and imidocarb dipropionate, have sometimes been reported to have toxic side effects 3 . In addition, DA-resistant Babesia gibsoni and the development of imidocarb dipropionate–resistant Theileria equi have been reported 4 , 5 . Therefore, less-toxic, low-cost and potent anti-piroplasm chemotherapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms for this change and the pharmacokinetics have not yet been unraveled, other factors in dog might affect the changing M121I population. It is also reported that three amino acid substitutions on cyt b related to ATV resistance were detected in a clinical case in Hyogo Prefecture [ 12 ]. These substitutions included M121I, and this dog received ATV treatment.…”
mentioning
confidence: 99%
“…Currently, chemotherapy treatments against piroplasmosis remain inadequate. Oxytetracycline, imidocarb dipropionate and diminazene aceturate (DA) are considered the main choices for the Pathogens 2020, 9, 127 2 of 14 treatment of piroplasm parasites that infect cattle and horses, although there have been cases of toxic effects related to these drugs [1,2], as well as the development of imidocarb dipropionate-resistant Theileria equi and DA-resistant Babesia gibsoni [3,4]. Combined atovaquone (AV) and azithromycin therapy is still the best choice against human zoonotic babesiosis due to its low side effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens 2020, 9, x FOR PEER REVIEW 2 of 14 effects related to these drugs [1,2], as well as the development of imidocarb dipropionate-resistant Theileria equi and DA-resistant Babesia gibsoni [3,4]. Combined atovaquone (AV) and azithromycin therapy is still the best choice against human zoonotic babesiosis due to its low side effects [5].…”
Section: Introductionmentioning
confidence: 99%